Exzessive Bodenerosion um und nach 1800. Zusammenfassender Bericht über ein südwestdeutsches Testgebiet - Hard, Gerhard (ERDKUNDE, 1970)
The following report refers to a test area in south west Germany which, during the time around and since 1800 has been characterised by a unique number of soil erosion occurrences, especially strong gully erosion. This intensification of soil erosion processes in the time period mentioned can, with the help of archival studies, be correlated with contemporaneous situations in agrarian history and the then composition of the cultivated area. Certain climatic fluctuations and long term changes in seasonal rythms, known to have occurred over approximately the same period, were on the other hand unimportant, being at most a strengthening factor. Without the specific agrarian situation the climatic factor would hardly have had any effect. It is suggested that the results can, in many points, be applied to broad areas of west and south west Germany and eastern France. A precondition for the intensification of soil erosion was the transition from an extensive alternating arable/ pasture economy to permanent arable on the entire field area, in the form of the three-field system (Zelgen) with about one-third ’black fallow’. With the transition to seasonal fallow (or to an alternating crop economy) gully erosion declined again and the beginnings of a major transition to permanent pasture in the second half of the 19th century also helped. The most important factors can also be reconstructed from archive material. Among others worthy of mention can be included: the giant crop parcels (Schlage) of the three-field system, not least the large areas of fallow; the particular ploughing techniques and their consequences for soil structure and soil water balance; the re-survey and re-distribution on geometrical lines of many fields around 1700, which took little notice of the dangers of erosion; the strong population pressure, above all since the end of the 18th century, which led to woodland clearance and the inclusion in arable land of even steep slopes. The following consequences of the accelerated soil erosion during the study period are discussed: 1. a complete alteration in the criteria for the assessment of soil quality; this revaluation in turn led, between about 1760 and 1840, to a redistribution of ownership between the rural social classes, 2. an accelerated out-migration rate in the districts and parishes particularly affected (especially among the lower peasant class), 3. anti-soil erosion protection measures which were partly of astonishing modernity (woodland planting, strip cropping, changes in crop rotation on erosion-sensitive slopes, etc.). The consequenes for (4) the microrelief of the arable area, (5) the mosaic of soil types in the contemporary cultural landscape and (6) the present vegetation pattern were particularly notable. The dead periglacial microrelief was most extensively reworked and given new forms by soil erosion. Sharp pedological boundary lines were created which today lie mainly under woodland and, at first sight, appear to be completely inexplicable. Finally, the soil erosion in the test area created the only present-day remnants of the so-called ’Steppenheide’ as well as many other individual traits in the pattern of contemporary vegetation. The latter two points are demonstrated with the help of individual examples.